Good Ancestors Practicing a Holistic Vision for Ecological Conversion - Procario-Foley, Carl B. (Religious education, 2022)
Since the publication of Pope Francis’ landmark encyclical (2015), Laudato Si, there has been a robust discussion among religious educators concerning the notion of ecological conversion. Drawing on this rich scholarship, this paper strives to move from the “what” of ecological conversion to the “how”; that is, how communities of faith might foster ecological conversion in holistic, integrated ways while honoring the breadth and depth of this important process of transformation.